Fire Forecasts July-September 2022 (Western Amazon) -Storymap English, Portuguese and Spanish - Castaño, Silvia-Elena; Carvajal, Andrea; Staiger Rivas, Simone; Zutta, Brian; Fernandes, Katia (2022)
Fires in the Amazon are the result of human activities, including the use of fire for deforestation, land clearing and agricultural maintenance. Most fires begin in non-forest areas that have already been cleared for agricultural use, but these fires can spread into neighboring forests and burn through the understory. Even these low-intensity surface fires kill most trees since Amazon forests have not adapted to fire. Fires in the Amazon are the result of human activities that (usually) begin with slash and burn practices to clear the land for to establish agro-pastoral activities. For the most part, fires occur over non-forest landscapes, but they can spill over into standing forest edges and burn the understory. https://storymaps.arcgis.com/stories/94794b38c5894fe088709cd1da64ab4a (English) https://storymaps.arcgis.com/stories/2fe5858e94924b9881c67b93ea5b6dd2 (Español) https://storymaps.arcgis.com/stories/94794b38c5894fe088709cd1da64ab4a (Português)